Pan-cancer analysis reveals dual roles of HES6 in cancer immunity and prognosis - Ying Sun; Peiru Liu; Dongyang Lv; Defu Yang; Shiyu Qiao; Jing Liu; Ying Yan; Wenping Wang (Discover Oncology)
Abstract A comprehensive pan-cancer analysis of HES6 was conducted to investigate the differential expression patterns, clinical implications, and prognostic significance of HES6 across multiple cancer types, while also aiming to elucidate the underlying biological mechanisms of HES6 in oncogenesis. HES6 plays a pivotal regulatory role in the progression of numerous malignant tumors, profoundly influencing the survival duration of patients with solid tumors and demonstrating a strong correlation with the immune microenvironment. Notably, HES6 is generally overexpressed in a wide range of cancer types, exhibiting significant divergence from its expression levels in normal tissues. Furthermore, HES6 has been found to serve as a predictive indicator of survival outcomes in patients with various solid tumors. The gene expression profile of HES6 and its associated genes is predominantly enriched in CD8 + T cells and macrophages. Additionally, HES6 and its cognate genes are significantly enriched within critical signaling cascades, including the “Epithelial-Mesenchymal Transition Pathway,” “NOTCH Signaling,” and the “Wnt signaling activation,” among others. HES6 may exert its influence on cellular function and oncogenic behaviors through interactions with HES1 and other proteins. It also demonstrates a robust association with a multitude of inflammation-related genes, immunomodulatory genes, and receptor genes across diverse cancer types. Based on these findings, it is hypothesized that HES6 may emerge as a potential clinical biomarker for solid tumors, particularly gliomas.